2022
DOI: 10.1101/2022.12.05.519186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of a strain-specific CD-1 reference genome reveals potential inter- and intra-strain functional variability

Abstract: Background: CD-1 is an outbred mouse stock that is frequently used in toxicology, pharmacology, and fundamental biomedical research. Although inbred strains are typically better suited for such studies due to minimal genetic variability, outbred stocks confer practical advantages over inbred strains, such as improved breeding performance and low cost. Knowledge of the full genetic variability of CD-1 would make it more useful in toxicology, pharmacology, and fundamental biomedical research. Results: We perform… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As such, they potentially contribute to the specie-specific characteristics of TESCO activity. In the same line, several studies have shown that TEs are highly heterogeneous between mouse strains (Nellaker et al, 2012;Jung et al, 2023) that can modify gene expression (Zhou et al, 2021) and chromatin dynamics (Ferraj et al, 2023). Therefore, we can speculate that strain-specific TEs could be involved in the sensitivity of a C57BL/6J background to sex reversal (Eicher et al, 1982;Eicher et al, 1996;Munger et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As such, they potentially contribute to the specie-specific characteristics of TESCO activity. In the same line, several studies have shown that TEs are highly heterogeneous between mouse strains (Nellaker et al, 2012;Jung et al, 2023) that can modify gene expression (Zhou et al, 2021) and chromatin dynamics (Ferraj et al, 2023). Therefore, we can speculate that strain-specific TEs could be involved in the sensitivity of a C57BL/6J background to sex reversal (Eicher et al, 1982;Eicher et al, 1996;Munger et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Concerning strain specificity, the motif composition might vary depending of the mouse strain and influence subsequent recognition by DNA-binding proteins as it has been shown for CTCF in the mouse CD-1 strain (Jung, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of transcriptomes of homozygous CAST/EiJ and C57BL/6J stem cells cultured in-house (see below), we downloaded raw reads and mapped them to the corresponding reference genome for the respective strain (CAST/EiJ or GRCm38). For validation of the role of candidate transcription factors in translation regulation in stem cells, we mapped RNA-seq from Ehmt2 knockout embryos (NCBI accession GSE71500; Auclair et al ., 2016) and their corresponding wild-type to the GRCm38 reference, and we mapped RNA-seq from Eed knockout stem cells and their corresponding wild-type to the CD-1 reference genome (NCBI accession GSE209815; Jung et al ., 2023).…”
Section: Methodsmentioning
confidence: 99%